A handbook for the standardised sampling of plant functional traits in disturbance-prone ecosystems, with a focus on open ecosystems (vol 68, pg 473, 2021) - Wigley, B. J.; Charles-Dominique, T.; Hempson, G. P.; Stevens, N.; te Beest, M.; Archibald, S.; Bond, W. J.; Bunney, K.; Coetsee, C.; Donaldson, J.; Fidelis, A. [UNESP]; Gao, X.; et al. (Csiro Publishing, 2021)
Plant functional traits provide a valuable tool to improve our understanding of ecological processes at a range of scales. Previous handbooks on plant functional traits have highlighted the importance of standardising measurements of traits to improve our understanding of ecological and evolutionary processes. In open ecosystems (i.e. grasslands, savannas, open woodlands and shrublands), traits related to disturbance (e.g. herbivory, drought, and fire) play a central role in explaining species performance and distributions and are the focus of this handbook. We provide brief descriptions of 34 traits and list important environmental filters and their relevance, provide detailed sampling methodologies and outline potential pitfalls for each trait. We have grouped traits according to plant functional type (grasses, forbs and woody plants) and, because demographic stages may experience different selective pressures, we have separated traits according to the different plant life stages (seedlings saplings and adults). We have attempted to not include traits that have been covered in previous handbooks except for where updates or additional information was considered beneficial.